FIQH INDONESIA: TRANSFORMASI DAN SINKRONISASI FIQH WASIAT DAN HIBAH DALAM KOMPILASI HUKUM ISLAM DI INDONESIA - Abu Syhabudin (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2017)
Compilation of Islamic Law (CIL) on the testament and grant it describes the sourcematerial of Fiqh. In particular testament and grant are discussed in Fiqh. The Fiqh of testament and grants with CIL there are similarities and differences. In the Fiqh, testament and grant the discussion based on the theory of knowledge, while the discussion CIL has been transformed into chapters, chapter and verse, these changes are shaped like laws and regulations (qanûn). Articles in CIL about testament and grant suspected to be the transformation of Fiqh as a result of diligence Indonesian clerics. However, there are several chapters and verses in CIL are not in synchronous (as appropriate) with the Fiqh. This study aims to examine the transformation of matter Fiqh on the testament and grant to the material provisions contained in CIL, analyzing synchronization between CIL materials with Fiqh, knowing synchronization CIL with the legal system in Indonesia, knowing the shape transformation on the testament and grant to the articles in CIL, and analyzing the Indonesian scholars diligence in transforming the material in the articles of CIL: age21 years, a testament to the heirs, grant one-third property, and the calculation of the grant from parents to children as inheritance. Based on the results of research conducted by the authors, it can be concluded that: 1) The articles contained in CIL about testament and grants is the transformation of Fiqh. 2) There is synchronization between the material articles of testament and grants in CIL with Fiqh and legal system in Indonesia. 3) There are two forms of transformation, namely a) The textual transformation that comes from the book of Fiqh. b) Transformation contextual sourced from Indonesian diligence scholars, including: provision of age 21 years, a testament to the heirs, grant one-third, and the calculation of the grant as a legacy. Key Word: Fiqh, Transformasi, Sinkronisasi, Wasiat, Hibah